Political Connections and Tax Avoidance - Tjahyadi, Sherin; Carolina, Verani (Universitas Kristen Maranatha, 2024)
Abstract Purpose - This study aims to find empirical evidence whether political connections affect tax avoidance. Design/methodology/approach - The research method used is a quantitative research method from annual reports and financial statements of primary consumption sector companies listed on the IDX (Indonesia Stock Exchange) for 2019-2021. The sampling method used is a non-probability sampling method (purposive sampling). This study used regression panel data processed using Eviews 12.Findings - the results showed that political connections affect tax avoidance.Research limitations/implications – Investors who wish to invest in a company may choose to invest in companies with political connections due to the minimal tax avoidance practices carried out in such companies. Keywords: Tax, Political Connections, and Tax Avoidance